Analisis Kompetensi Manajerial Kepala Sekolah dalam Perencanaan Peningkatan Mutu Pendidikan Menengah Kejuruan - Amon, Lorensius; Harliansyah, Harliansyah (Lembaga Pengembangan Kinerja Dosen, 2022)
This article focuses on the managerial competence of principals. More specifically, it discusses the planning, implementation, monitoring and obstacles in improving the quality of education in vocational high schools in Samarinda City. This study uses a qualitative approach with a descriptive method. Observation, interview and documentation techniques were used to collect data, then analyzed through the process of data reduction, data presentation, and drawing conclusions. The findings indicate that the principal's managerial competence planning is carried out based on the vision, mission, school goals, and needs. The principal involves all elements of the academic community in planning school improvement and development. Planning to increase teacher professionalism is carried out in work meetings and described in strategic plans and school operational plans. Aspects of assessment in educational supervision are teacher attendance, teacher performance in schools, student development, lesson plans, and syllabus. The obstacle is competence in keeping up with the latest technology. Thus, this article contributes to knowledge about managerial competence as well as managerialism.